1991
DOI: 10.1111/j.1095-8649.1991.tb04383.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and community analysis of the parasite fauna of juvenile spot, Leiostomus xanthurus (Lacepede), and Atlantic croaker, Micropogonias undulatus (Linnaeus), Sciaenidae) in two estuaries along the middle Atlantic coast of the United States

Abstract: The parasite communities ofjuvenile spot, Leiostomu.F.uanthurus Lacepi.de, and Atlantic croaker, Micropogonias undulutus (Linnaeus), changed with size, season. and geographical area. A total of 2 1 parasitic species occurred in juvenile spot and 19 occurred in juvenile croaker from Chesapeake Bay and Pamlico Sound. More parasitic species were acquired as juveniles grew, diversified their diets, and consumed larger numbers of intermediate hosts. They were also exposed to infective larvae of parasites with direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
3
14
0
1
Order By: Relevance
“…Differences found between prevalence and mean intensity of parasites of P. corruscans and S. borelli are in accordance to Thoney (1991) who observed that these variations in different host species may be explained by their alimentary habits. According to Kennedy et al (1986) a greater diversity of prey items contributes significantly to an increase in the number of specimens of parasites, justifying the results obtained in the present research work with regard to P. corruscans.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Differences found between prevalence and mean intensity of parasites of P. corruscans and S. borelli are in accordance to Thoney (1991) who observed that these variations in different host species may be explained by their alimentary habits. According to Kennedy et al (1986) a greater diversity of prey items contributes significantly to an increase in the number of specimens of parasites, justifying the results obtained in the present research work with regard to P. corruscans.…”
Section: Discussionsupporting
confidence: 91%
“…Since the populational fluctuation of intermediate hosts can influence the occurrence of heteroxenous parasites (Thoney 1991) the high prevalence of infection, especially in P. corruscans, suggests the availability of its intermediate hosts as preys and thus important determinants of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the patterns detected by Thoney (1991Thoney ( , 1993 in the parasite infracommunities of M. undulatus (Linnaeus) from North American Atlantic Ocean, are close to those detected in M. furnieri. According to Thoney (1991Thoney ( , 1993, the parasite community of M. undulatus is dominated by endoparasites and the young fishes showed similar parasite diversity in relation to adults croakers, but the parasites recorded by Thoney (1991Thoney ( , 1993 showed higher values of prevalence and parasite abundance.…”
Section: Discussionmentioning
confidence: 87%
“…According to Thoney (1991Thoney ( , 1993, the parasite community of M. undulatus is dominated by endoparasites and the young fishes showed similar parasite diversity in relation to adults croakers, but the parasites recorded by Thoney (1991Thoney ( , 1993 showed higher values of prevalence and parasite abundance. Luque (1996), and Oliva and Luque (1998) studied the characteristics of the parasite infracommunities in five sciaenids from Peru, in the South American Pacific Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Thoney (1991Thoney ( , 1993 recorded it from the same host at the Chesapeake Bay and the Palmico Sound, North Carolina.…”
Section: Discussionmentioning
confidence: 99%